Uveitis Intermediet dengan Glaukoma Sekunder Okuli Sinistra - Desty Marini; Rani Himayani; Helmi Ismunandar (CV. Jasa Sukses Abadi, 2020)
Uveitis is inflammation that occurs in the uvea tract. Intermediate uveitis is inflammation of the vitreous body, the retinal blood vessels. The most caused of secondary glaucoma is inflammation of the eye. Glaucoma is one thah cause increases intraocular pressure causing optic nerve damage and interference with the visual loss. Case description, female patients within 32 years came with the main complaint that the left eye visual loss since one week ago. Complaints the patients are headache, nausea, vomiting at three times, and glare when the eyes exposed to sunlight. Headache especially in the left eyelid. Wearing glasses (+), red eye history (+). Ophthalmological examination found on right eye visus 2/60, left eye visus 1/300, right eye intraocular pressure 10mmHg and left eye 58mmHg. Examination of the anterior segment of the right eye was within normal, anterior segment of the left eye was palpebra pseudoptosis, fornix and bulbi, tarsal conjunctiva injection, ciliary injection, corneal edema, precipitous keratic, deep anterior chamber, hypopion of zero point five millimeters, pupil dilatation, iris kripta, pupillary reflexes, the lens, vitreous not visible because the media was heavy. The mechanism of IOP increase in open-angle glaucoma caused by uveitis were hypersecretion, blockage of the trabecular meshwork, inflammation of the trabecular meshwork, trabeculum and endothelium damage, and glaucoma caused long-term use corticosteroids. Treatment used was carbonic anhydrase inhibitors, beta adrenergic inhibitors, topical and systemic anti-inflammatory drugs.